Corporate environmental infringement, legal regulation, and sustainable development: punitive damages as a perspective - Li, Ziwei; Wang, Xingyu; Wu, Zhuang (Frontiers in Environmental Science, 2024)
In order to maximize personal interests, enterprises have a tendency to choose environmental pollution in exchange for corporate profits, resulting in negative externalities, the Civil Code of the People's Republic of China on the environmental infringement of enterprises to impose legal regulations, in order to achieve the maximization of the use of the allocation of social resources, and to promote the sustainable development of society. Subsequent judicial interpretations have set a two-fold cap on the amount of punitive damages. However, in cases of extremely serious environmental damage, the two-fold cap on punitive damages for environmental infringement will create the possibility of insufficient compensation. Based on this, this paper analyzes the legal text of China's punitive damages provisions for environmental infringement, and analyzes the interrelationships between enterprises, and between enterprises and potential environmental infringement victims in a game analysis. The results of the analysis show that as the amount of punitive damages for environmental infringement increases, the probability of the infringed person filing a lawsuit and the probability of the enterprise reducing its environmental infringement behavior also increase. In order to promote the cause of China's sustainable development, this paper puts forward relevant suggestions for the improvement of China's environmental legal regulation: firstly, the upper limit of the amount of punitive damages for environmental infringement should be canceled; secondly, the amount of reasonable punitive damages should be set on the basis of the damages caused by environmental infringement on human beings and the environment; lastly, in the baseline setting of the amount of punitive damages, additional factors need to be taken into account, and the amount of punitive damages should be set for the enterprises with a high degree of maliciousness. Finally, additional factors need to be considered in setting the benchmark for the amount of punitive damages, which should penalize the environmental infringement enterprises with a high degree of malice with heavier penalties, and at the same time can penalize the enterprises with smaller scale of operation and economic strength with lighter penalties.